The vibration-rotation of H2O and its complexation with CO2 in solid argon revisited: Spectroscopy in Cryocrystals and Matrices - Michaut, Xavier; Vasserot, Anne-Marie; Abouaf-Marguin, Luce (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2003)
Fourier-transform infrared spectroscopy in the frequency range 400–4000 cm–1 has been used toinvestigate the absorption of H2O and H2O:CO2 complex isolated in solid argon. Thanks to the lowest temperature reached in our experiment, temperature effects and nuclear spin conversion studies allow us to propose a new assignment of the rovibrational lines in the bending band n2 for the quasi-freely rotating H2O. An additional wide structure observed in this band shows two maxima around 1657.4 and 1661.3 cm–1, with nuclear spin conversion of the high frequency part intothe low frequency one. This structure is tentatively attributed to a rotation-ranslation coupling of the molecule in the cage. However, the equivalent effect is not observed in the vibrational stretchingbands n1 and n3. Finally, by double doping experiments with CO2, important new structures appear, leading us to unambiguously extract the frequencies of the lines of the H2O:CO2 complex.